Gadai Syariah di Indonesia : konsep, implementasi, dan institusionalisasi - Anshori, Abdul Ghofur (Bulaksumur, Yogyakarta : Gadjah Mada University Press, 2006)
Implementation and institutionalization of Islamic mortgage law in Indonesian legal system
Mengandungi daftar pustaka (p. [171]-173) dan indeks
Keywords: Mortgages (Islamic law) -- Indonesia; Banks and banking -- Indonesia -- Religious aspects -- Islam; Banking law (Islamic law) -- Indonesia